Quantifying Systemic Risk in the Presence of Unlisted Banks: Application to the Dutch Financial Sector - Daniel Dimitrov; Sweder van Wijnbergen (Tinbergen Institute, 2022)
We propose a credit portfolio approach for evaluating systemic risk and attributing it across institutions. We construct a model that can be estimated from high-frequency CDS data. This captures risks from privately held institutions and cooperative banks, extending approaches that rely on information from the public equity market. We account for correlated losses between the institutions, overcoming a modeling weakness in earlier studies. A latent risk factor with heterogeneous exposures fitted on the implied default probabilities quantifies the potential for joint distress and losses. We apply the model to a universe of Dutch banks and insurers.
Keywords: G01; G20; G18; G38; 330; Systemic risk; CDS rates; implied market measures; financial institutions